Evaluation of band gap energy of TiO2 precipitated from titanium sulphate - Landi Jr., Salmon (2022)
The determination of the band gap energy () of semiconductors powder materials can be performed from diffuse reflectance spectroscopy (DRS) measurements. For this purpose, the classical theory proposed by Kubelka and Munk (K-M) and the so-called plot Tauc, both discussed here, have been largely employed. We investigate the values of anatase TiO2 particles synthesized by precipitation of titanyl sulphate in the presence of 5% ammonia solution and titanium and iron salts. Based on K-M function and Tauc plot and considering that the TiO2 anatase phase is an indirect band gap semiconductor, our results indicate that the samples subjected to a mechanochemical treatment (mill rotation speed equal to 300 rpm) present substantially lower values compared to those reported by other authors in a recent work